2020
DOI: 10.1002/crt2.12
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein, delirium, and other psychological symptoms among patients with advanced cancer

Abstract: BackgroundIt remains unclear whether a relationship exists between elevated C‐reactive protein (CRP) levels and delirium. The primary aim was to investigate the relationship between CRP and delirium in advanced cancer.MethodsThis study was a multicenter prospective cohort study conducted in palliative care units. At baseline, the physicians diagnosed delirium. On the seventh day, they evaluated whether new delirium had occurred. Subjects were divided into four groups according to CRP levels. We assessed the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 52 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…The study also showed that drowsiness was significantly worse with increasing CRP levels [3]. Delirium was diagnosed with the Diagnostic and Statistical Manual of Mental Disorders 5th edition (DSM-5), and drowsiness was estimated on the Japanese version of the Integrated Palliative care Outcome Scale (IPOS) [3]. The findings implied that the impact of systemic inflammation on the CNS might be one of the contributing factors to the genesis of psychological symptoms of illness.…”
Section: Limited Information Is Currently Available On the Relationsh...mentioning
confidence: 98%
See 4 more Smart Citations
“…The study also showed that drowsiness was significantly worse with increasing CRP levels [3]. Delirium was diagnosed with the Diagnostic and Statistical Manual of Mental Disorders 5th edition (DSM-5), and drowsiness was estimated on the Japanese version of the Integrated Palliative care Outcome Scale (IPOS) [3]. The findings implied that the impact of systemic inflammation on the CNS might be one of the contributing factors to the genesis of psychological symptoms of illness.…”
Section: Limited Information Is Currently Available On the Relationsh...mentioning
confidence: 98%
“…The CNS is directly affected by inflammatory mediators in sickness, and the brain mediates cluster of behavioral changes (e.g., sleep disruption, cognitive impairment and memory deficits, disorientation, and reduction in motivated behavior) through communication systems between the immune system and the brain in humans and animals [20]. Other outcomes of sickness behavior, including weight loss (reduction of skeletal muscle mass and fat mass), increased catabolism (increased proteolysis and lipolysis), circadian rhythm disorders (disarrangement of eating habits and sleep-wake cycles), social disinterest, and sexual disinterest, appear to be a part of an integrated response of CNS and systemic inflammation [2,3,4 ▪▪ ,5,6,19,20].…”
Section: Rethinking Patient Experience Of Cancer Cachexia: Cancer Cac...mentioning
confidence: 99%
See 3 more Smart Citations